The role of the criminological characteristics of the mafia in Italian criminal law – with particular reference to the application of judicial law (Academic Journal of Internal Affairs, 2024)
The aim of the study is to highlight the different nature of the criminology-legislation-application of the law in Italy compared to the domestic criminal law, at least in the case of mafia cases.
Keywords: mafia; italian; criminology